Occurrence of toxin genes in Staphylococcus pseudintermedius from diseased dogs and other domestic and wild species - Leticia Camara Pitchenin; Laila Natasha Santos Brandão; Janaina Marcela Assunção Rosa; Francielle Cristina Kagueyama; Alvair da Silva Alves; Ícaro Sergio Magalães Rocha; Luciano Nakazato; Valéria Dutra (Journal of Infection in Developing Countries)
Introduction: Staphylococcus pseudintermedius is coagulase-positive species of the Staphylococcus intermedius group. It is an opportunistic pathogen that can cause infection in various parts of the body and has a zoonotic potential. Although studies on the pathogenicity and epidemiology of S. pseudintermedius are limited, it is known that this bacterium has several virulence factors, including toxins. These toxins can be classified into three main groups: pyrogenic toxins with superantigenic properties such as toxic shock syndrome toxin and staphylococcal enterotoxins, exfoliative toxins, and cytotoxins  such as hemolysins and leukocidins.